2013
DOI: 10.1155/2013/608654
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Dysregulation in Psychiatric Disease

Abstract: Microglia, the brain's resident immune cells, are phagocytes of the macrophage lineage that have a key role in responding to inflammation and immune challenge in the brain. More recently, they have been shown to have a number of important roles beyond immune surveillance and response, including synaptic pruning during development and the support of adult neurogenesis. Microglial abnormalities have been found in several neuropsychiatric conditions, though in most cases it remains unclear whether these are causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
189
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(197 citation statements)
references
References 110 publications
4
189
0
4
Order By: Relevance
“…A review (Frick et al, 2013) detailing studies concerning cytokine effects on different immune cells indicated that data on microglial dysregulation are "limited" and reported mixed results relating to increased microglial densities and activation in diagnosed MDD patients in both clinical and post-mortem examinations. However, the review also found that aggregated animal studies commonly implicated microglial activation with depressive phenotypes in rats that undergo chronic psychological stress, neonatal LPS injection, and mice with CX3CR1 (fractalkine receptor) deficiencies.…”
Section: The Inflammatory Process and Hypothesis In Mddmentioning
confidence: 99%
“…A review (Frick et al, 2013) detailing studies concerning cytokine effects on different immune cells indicated that data on microglial dysregulation are "limited" and reported mixed results relating to increased microglial densities and activation in diagnosed MDD patients in both clinical and post-mortem examinations. However, the review also found that aggregated animal studies commonly implicated microglial activation with depressive phenotypes in rats that undergo chronic psychological stress, neonatal LPS injection, and mice with CX3CR1 (fractalkine receptor) deficiencies.…”
Section: The Inflammatory Process and Hypothesis In Mddmentioning
confidence: 99%
“…Mi croglia are the resident macrophages of the central nervous system (1). These immune cells are activated by inflammatory stimuli, such as pathogens or neuronal damage, and initiate a cascade of inflammatory responses.…”
mentioning
confidence: 99%
“…The presence of dysregulated microglia is evident in the development of psychiatric disorders, such as schizophrenia, anxiety and major depression disorder (Frick et al, 2013;Réus et al, 2015), and an increase in microglial density correlates with suicide rates of different neuropsychiatric disorders (Mondelli et al, 2015). Emerging evidences point the possible role of microglial in BD pathology as inducers of neuroinflammation via kynurenine pathway.…”
Section: The Role Of Microglial Inflammatory Process In Bipolar Disordermentioning
confidence: 99%
“…On the other hand, Frick and coworkers proposed different functions of microglia in psychiatric disorders (Frick et al, 2013), such as alterations in microglial function at sites where neurogenesis, neuronal function and homeostasis are affected, leading to either neuronal or synaptic dysfunctions instead of neurodegeneration. However, the exact involvement of microglial cells in psychiatric disorders remains very debatable.…”
Section: The Role Of Microglial Inflammatory Process In Bipolar Disordermentioning
confidence: 99%